2021
DOI: 10.3390/healthcare9030364
|View full text |Cite
|
Sign up to set email alerts
|

Dentists’ Working Conditions during the First COVID-19 Pandemic Lockdown: An Online Survey

Abstract: The aim of this study was to investigate the operating conditions of dentists in Central Europe during the first coronavirus disease 2019 (COVID-19) lockdown. A survey including 24 questions was emailed to dentists in Austria, Germany, Switzerland and South Tyrol (Italy). Questions regarding dentists’ field of work, working hours, treatments performed, personal protective equipment and protocols, and economic consequences were asked. 1731 participants were included. 30.4% of participants worked mainly in Austr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
2
8
0
9
Order By: Relevance
“…Our study found a reduction in the number of admitted patients during the first wave of the pandemic, which is consistent with other studies [9,39,[46][47][48][49][50]. Earlier research on the Polish dentists conducted at the beginning of the pandemic showed that as many as 71.2% of them completely suspended their practice in response to the pandemic [9].…”
Section: Discussion and Additional Resultssupporting
confidence: 92%
“…Our study found a reduction in the number of admitted patients during the first wave of the pandemic, which is consistent with other studies [9,39,[46][47][48][49][50]. Earlier research on the Polish dentists conducted at the beginning of the pandemic showed that as many as 71.2% of them completely suspended their practice in response to the pandemic [9].…”
Section: Discussion and Additional Resultssupporting
confidence: 92%
“…The high risk of infection in the dental working conditions in Austria, Germany and Switzerland was acknowledged in this study as well as the need of evaluation of the number of infections among dentists in other European countries was mentioned. Also previously mentioned studies suggest more researches on the influence of pandemic on dental working environment should be carried out [ 8 , 9 , 15 ]. Thus our study reports data from two countries in Europe and allows making primary conclusions on how the working conditions of the dentists were affected by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The range of dental services provided in the office as part of general primary care, dental surgery, paediatric dentistry and conservative dentistry was limited to procedures necessary in cases of urgent need for intervention: i.e. pain, inflammation and purulent processes, injuries, cysts, and conditions with risk of complications in patients 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%